PENGGUNAAN AKUNTANSI DASAR UMKM PADA PEMBUATAN LAPORAN KEUANGAN PENGUSAHA SARUNG DI KECAMATAN MAJALAYA KABUPATEN BANDUNG - Ari Bramasto; Puti Harissa; Sri Dewi Anggadini (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2022)
Lack of knowledge of the use of financial statements, difficulties in using financial statement applications, limited product marketing problems. CV. Mekar Jaya, as a form of individual business in Majalaya, Bandung Regency, has experienced these various problems. Whereas the application of accounting in Micro, Small and Medium Enterprises (MSMEs) is recording and decision making as well as long-term planning for MSMEs control tools to avoid spending outside of MSME planning and even to be able to find out debts to other parties. CV. Mekar Jaya are still not able to make their financial statements. The purpose of this Community Service Program is the implementation of orderly administration of MSME Financial Reports. The implementation method to overcome problems is by socializing the benefits and importance of financial reports for CV. Mekar Jaya, training on the use of Excel applications and other alternatives using the LAMIKRO application, assistance every weekend for 2 months so that they can report the Balance Sheet (Financial Position), Profit and Loss Report and Statement of Changes in Capital. The results of these financial statements can be used by CV. Mekar Jaya in making financial decisions, controlling business operational costs, knowing accounts payable, calculating taxes, and so on. Mandatory Outputs are expected by publication on social media, journals, and online news, while additional outputs are submitted in the form of Simple Copyright. Key words: Financial Statements, Micro, Small and Medium Enterprises